Technological Update to the Criminal Codes – Essential Use of Audio-Visual Technology (Maharaja Surajmal Institute Law Journal, 2024)
India witnessed a watershed moment and created history when on July 01,2024  it introduced new criminal codes with an objective and intention to reform and  upgrade its criminal justice system. The Indian Ministry of Home Affairs declared  the implementation of the three new criminal statutes, namely Bhartiya Nagrik  Suraksha Sanhita, 2023, Bharatiya Nyaya Sanhita, 2023, and Bhartiya Sakshya  Adhiniyam, 2023, enforced on July 1, 2024. The British era Indian Penal Code, the  Code of Criminal Procedure, and the Indian Evidence Act, respectively were thus  repealed by the new codes.. The prime objective of the new codes is to modernise  and substitute the outdated colonial laws by prioritising the implementation of  justice with a victim-centred approach. They also aim to enhance national security  and introduce reviews of digital/electronic evidence as key aspects of these laws.  The bill introduced in parliament included a statement of objects and reasons that  criticised the CrPC for several issues, including delays in delivering justice, complex  procedures, a large backlog of cases, low conviction rates, and inadequate use of  technology and forensic methods. The BNSS strives to alleviate such problems.  This article examines a specific goal of the BNSS, which aims to enhance and speed  up the justice delivery system through the compulsory integration of electronic  communication and audio-visual technologies in different legal procedures. The  article is divided into three parts. Prior to conclusion the Part 1 introduces the  concept note of the Article and lays the foundation of the article. Thereafter, Part 2  draws a comparative insight between provisions of the CrPC and the BNSS on the  use of audio-video technology. Part 3 provides an in depth analysis of the newly  added provisions related to the use of audio-video technology. This research aims  to provide clarity on the newly added provisions and becomes relevant for the  policy makers, the investigating agencies, lawyers and other stakeholders.
Keywords: ACriminal Justice System; Reforms; Electronic Communication; Audio Visual Technology; Bharatiya Nagrik Suraksha Sanhita 2023 and Criminal Procedure Code